2020
DOI: 10.1182/blood-2020-137088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Transfusion Transmissible Infections Among Blood Donors and Associated Safety Challenges in Pakistan

Abstract: Introduction: The blood transfusion (BT) system in Pakistan is fragmented, demand-driven, and depends on weakly regulated transfusion practices. This is primarily a big problem in smaller cities and remote rural areas. Pakistan has one of the highest hepatitis B virus (HBV) and hepatitis C virus (HCV) prevalence worldwide, estimated around 5 & 10 million cases, respectively. There is a considerable risk that transfusion-transmissible infections (TTIs) may have contributed to the current epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(85 reference statements)
0
12
1
Order By: Relevance
“…At least in the small sample of bone marrow samples found positive for malaria, the even rarer numbers lacking parasites on peripheral blood smear suggests that infection of bone marrow without parasitaemia may be the exception. A systematic review of infections among blood donors during 2010 to 2020 in Pakistan found 0.11 % positive for malaria [32]. It cannot be known if invasion of blood by the Plasmodium is usually attended by infection bone marrow, the similarities of those rates of infection of blood and bone marrow suggests that may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…At least in the small sample of bone marrow samples found positive for malaria, the even rarer numbers lacking parasites on peripheral blood smear suggests that infection of bone marrow without parasitaemia may be the exception. A systematic review of infections among blood donors during 2010 to 2020 in Pakistan found 0.11 % positive for malaria [32]. It cannot be known if invasion of blood by the Plasmodium is usually attended by infection bone marrow, the similarities of those rates of infection of blood and bone marrow suggests that may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…At present, malaria is endemic in the region, with 3.5 million cases reported every year. 11 The unsafe blood transfusion practices resulting in transmission of infected blood are further fueling these numbers. A recent systematic review by Ehsan et al reports that the seroprevalences of HBV and HCV among the blood donor population of Pakistan were 2.04% and 2.44%, respectively, and 70% of all donors who tested positive for TTIs had a history of blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the studies included in this review that had a large number of replacement donors reported a higher prevalence of TTIs when compared with the studies with a high number of voluntary nonremunerated donations (VNRDs). 11 Moreover, there have been recent reports of isolated low-scale epidemics of HIV in rural areas of Pakistan, and a systematic review by Rabold et al has identified iatrogenic transmission, such as unsafe blood transfusions and reuse of medical equipment like syringes, as the primary contributing risk factor for the spread of HIV in the country. 12 Regular blood transfusions are the mainstay of treatment of patients with blood disorders such as thalassemia and anemia, and are also widely used for the management of acute trauma, surgeries, hemorrhage, and complications related to childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Also this result was comparatively lower than other countries like, Abdelaziz (2020) detected that the prevalence of HBV among blood donors in Sudan was 1.3%. And Ehsan et al (2020) detected that the prevalence of HBV among blood donors in Pakistan was 2.04% (using ELISA technique detected HBsAg). While the result of HCV in blood donors in Wasit Province was 4.0%, the present study demonstrated an increase in anti-HCV with time which is considerable higher than that reported by other Iraqi researcher like Al-Sadi and Abdul-Jalil in 2016 reported that the prevalence of hepatitis C virus among blood donors was 2.8% in Basra governorate.…”
Section: Discussionmentioning
confidence: 99%